In-silico studies for targeting PPARγ for the Type II Diabetes Mellitus. (2022) - Reetu, Reetu; Garg, Aakriti; Roy, Kuldeep K.; Roy, Anupam; Gupta, Sreya; Malakar, Chandi C.
Graphical abstract: Abstract: The virtual molecular library contains phenolic group at the intermediate stage was investigated which having a potency to treat Type 2 Diabetes Mellitus. The designed molecules have shown comparable in-silico binding affinity to marketed thiazolidinedione (TZD) class of drug toward peroxisome proliferator activated receptor-γ (PPAR-γ) protein. Interestingly, change of phenolic group with 5-hydroxy quinolone in pioglitazone has shown high structural conservation in PPAR-γ ligand binding domain (LBD) with pioglitazone having better affinity. This information might be very useful to identify novel lead compounds for further development toward Type 2 Diabetes Mellitus treatment targeting PPAR-γ.